Borrowing as a way of enrichment of the tourism terminology in the Russian language - Balmagambetova, Zh.T.; Ayupova, G.K.; Karimbek, A.E. (KU Publ., 2022)
The article deals with the problems of vocabulary enrichment with foreign vocabulary. Borrowings, on the one hand, are the source of enrichment of the vocabulary of the language, and on the other hand, they are an integral part of the terminology system in many areas of knowledge. The main donor languages in Russian and English languages were analyzed. Intra-linguistic and extralinguistic reasons and factors of borrowing were identified. The analysis of the terminological systems of the tourism sphere of the English and Russian languages showed that borrowings in both languages can be divided into three classes: borrowings proper (direct borrowings), calques (indirect borrowings) and hybrid formations. The analysis of foreign language inclusions in the terminology of tourism in Russian was carried out. Based on the classification of scientists, subgroups of foreign language inclusions in the Russian terminology of the tourism sector were identified from the corpus of the analyzed units. The analysis showed that most borrowings of the tourism term system go through two stages of adaptation to the Russian language system: “entering” the receiving language (phonetic and graphic level) and the actual development of the borrowed term by the receiving language (semantic level).
Кірме сөздер орыс тіліндегі туризм терминологиясын байыту көзі ретінде
Заимствование как способ обогащения терминологии туризма в русском языке
Keywords: borrowings; inclusions; calques; terminology; terminology system